Information transparency, fairness and labor market efficiency - Ebru Isgin; Barry Sopher (Rutgers University, Department of Economics, 2013)
The paper studies the role of information transparency on fairness concerns, welfare and efficiency. When the firm's productivity and ultimately profits are revealed, wage offers induce relatively fair divisions of potential gains and workers respond with higher performance. Workers respond not only to wages but also to firms' intentions concerning fairness. Information transparency serves as a mechanism that promotes fairness and performance while the lack of transparency results in reduced earnings for workers and market inefficiency.
Keywords: C9; D8; J; 330; Experiments; Incomplete Contracts; Fairness; Information Transparency; experimental economics; incomplete contracts; fairness; information transparency